A new Vanilla species from Peninsular Malaysia - Raffi, Akmal; Abdullah, Nur Ashikin Psyquay; Abdullah, Thohirah Lee; Go, Rusea (Malaysian Nature Society, 2017)
A new species, Vanilla sanguineovenosa R. Go & A. Raffi, from Peninsular Malaysia is described, illustrated, and other aspects of interest discussed. It is so far known from a small population in lower montane forests at Tapah, Perak. A field key to the Peninsular Malaysian taxa, including V. sumatrana is also provided.